2012
DOI: 10.1186/1471-2377-12-1
|View full text |Cite
|
Sign up to set email alerts
|

No effect of recumbency duration on the occurrence of post-lumbar puncture headache with a 22G cutting needle

Abstract: BackgroundSupine recumbence has been widely performed to prevent post-lumbar puncture headache (PLPH). However, the optimal duration of supine recumbence is controversial. The aim of the study is to compare the occurrence of PLPH according to the duration of supine recumbence in patients with neurological disorders.MethodsA non-equivalent control/experimental pre-/post-test study design was used. Seventy consecutive patients were prospectively enrolled between July 2007 and July 2008. Thirty-five patients unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
75
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(87 citation statements)
references
References 19 publications
9
75
0
3
Order By: Relevance
“…These studies found that the amount of CSF removed during spinal tap, the CSF opening pressure and the length of time of bed rest after dural puncture do not influence the incidence of PDPH. 5,32 The position in which lumbar puncture is performed and the time in sitting position after injection of local anaesthetics were also found not to influence the incidence of PDPH. 33 Similarly, there appears to be no evidence that antiseptic agents used for cleaning the skin and the types of local anaesthetic agents have any role in the pathogenesis of PDPH.…”
Section: Other Possible Risk Factors For Pdphmentioning
confidence: 97%
“…These studies found that the amount of CSF removed during spinal tap, the CSF opening pressure and the length of time of bed rest after dural puncture do not influence the incidence of PDPH. 5,32 The position in which lumbar puncture is performed and the time in sitting position after injection of local anaesthetics were also found not to influence the incidence of PDPH. 33 Similarly, there appears to be no evidence that antiseptic agents used for cleaning the skin and the types of local anaesthetic agents have any role in the pathogenesis of PDPH.…”
Section: Other Possible Risk Factors For Pdphmentioning
confidence: 97%
“…However, because cognitive effects are secondary to biological changes in the brain, an appropriate biological test might more accurately reflect the disease process. Much recent work seeks to make AD diagnoses or predictions based on biological markers (Convit, de Asis, de Leon, Tarshish, De Santi, & Rusinek, 2000; Visser, Verhey, Hofman, Scheltens, & Jolles, 2002; Devanand, et al, 2008; Walhovd, et al, 2010; Clark & ADNI, 2011; Cui, et al, 2011; Furney, et al, 2011; Palmqvist, et al, 2012; Ye, et al, 2012; Zhang, Shen, & ADNI, 2012). Among the studies cited here that incorporate biological tests, those that include some form of cross-validation or a separate test set report accuracies ranging from 62% to 85%.…”
Section: Introductionmentioning
confidence: 99%
“…Hay estudios que reportan una asociación no significativa entre el número de intentos de punciones durales y la CPPD 6,24,31,32,34,46 . Sin embargo, Seeberger y cols realizaron un estudio prospectivo con 8034 punciones durales encontrando asociación estadística, estos autores atribuyen la falta de consistencia de los resultados en estudios anteriores debido a un bajo poder estadístico 47 .…”
unclassified
“…Del mismo modo, no hay diferencia estadísticamente significativa de la prevalencia de CPPD entre reposo en decúbito supino y deambulación precoz posterior a la punción dural 46,48,49 . Así mismo, un estudio prospectivo realizado en una muestra pequeña …”
unclassified